Revitalisasi Agama dan Budaya oleh Abuya Zahmir BA di Hiang Tinggi, Kabupaten Kerinci, Provinsi Jambi - Dina Afrijulianti; Ahmad Taufik Hidayat; Arwemi (Majalah Ilmiah Tabuah: Ta`limat, Budaya, Agama dan Humaniora, 2024)
Modernization and globalization have marginalized many traditional values, making the need for cultural and religious revitalization even more urgent. Religious figures such as Abuya Zahmir Ba play an important role as the guardian of religious values as well as the driving force in reviving the almost forgotten local traditions in Hiang Tinggi. The purpose of this article is to explain the contribution of Abuya Zahmir BA in the revitalization of religion and culture in Hiang Tinggi. This research uses historical research methods with the first step being heuristics, which is the collection of data from various relevant sources. The second step is source criticism, which involves verifying and checking the authenticity and credibility of the data. Next, the interpretation step is applied to interpret the data that has been collected. The final step is historiography, where the results of the research are organized in a scientific writing format. The results show that firstly, as an influential religious figure, Abuya Zahmir BA plays an important role in shaping the social order of society, especially in the field of social religion and moral values. Secondly Abuya Zahmir BA not only teaches religious knowledge, but also mobilizes solidarity and togetherness in Hiang Tinggi, as well as preserving the cultural heritage and spirituality of the village. Thirdly, his contribution was significant in shaping the character of the community, raising spiritual awareness, and connecting religious values with cultural traditions.